Konsep Akhlak dalam Islam dan Kontribusinya Terhadap Konseptualisasi Pendidikan Dasar Islam - Ahmad Sahnan (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper discusses akhlak concept and it`s conceptualization of Islamic primary school. In Islam akhlak occupy a very vital position because it involves horizontal and vertical relations. Likewise in Islamic primary school akhlak becomes a pillar on other pillars. Akhlak determination is very important in setting educational goals, teaching practices, methods, infrastructure, values that are instilled and all implementation. When akhlak and values of Islam are not contained in education, it is certain that the pillars of education are impossible to realize properly. The akhlak contribution in the conceptualization of Islamic primary school; first, help formulate educational goals. Second, help in formulating the characteristics and content of the curriculum. Third, help formulate the characteristics of professional teachers. Fourth, help formulate a code of ethics and school discipline. Fifth, make teaching and learning activities that produce students have noble character. Sixth, creating a clean, orderly, safe, peaceful, comfortable, and conducive learning environment. Realization of the concept can be started with further teaching followed by habituation education, exemplary, practice, coupled with examples, as well as explanations, coaching to finally become characters